2009
DOI: 10.1016/j.ecolecon.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Environmental amenities and optimal agricultural land use: The case of Israel

Abstract: This paper evaluates the effectiveness of changing land allocation among crops as a mechanism for increasing social welfare, where production profits and amenity benefits are augmented. A positive mathematical programming model is calibrated and applied to the northern part of Israel, using a crop-discriminating amenity-benefits function. Changes in land allocation increase social welfare by 2.4% nationwide, and by up to 15% on the regional level. Regional scale farming-profit losses amount to up to 6%. Due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Other applications include the estimation of the economic value of water and land (Howitt et al, 2001;Iglesias and Blanco, 2008;Medellín-Azuara et al, 2009;Kan et al, 2009), and climate change impacts (Henseler et al, 2009;Howitt et al, 2010;Medellín-Azuara et al, 2011;Howitt et al, 2012) (for reviews of other case studies see Heckelei et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other applications include the estimation of the economic value of water and land (Howitt et al, 2001;Iglesias and Blanco, 2008;Medellín-Azuara et al, 2009;Kan et al, 2009), and climate change impacts (Henseler et al, 2009;Howitt et al, 2010;Medellín-Azuara et al, 2011;Howitt et al, 2012) (for reviews of other case studies see Heckelei et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we adopt projections of three General Circulation Models (GCMs) and four representative concentration pathways (RCPs) to simulate climatic conditions in the 15 agricultural regions for the periods 2041-2060 and 2061-2080. Third, we extend the regional PMP model VALUE (Vegetative Agriculture Land Use Economic) (Kan et al 2009;Palatnik et al 2011) to explicitly include the effect of CO 2 concentration and temperature on agricultural production. 1 Finally, we implement the extended model to investigate impacts of the forecasted climate change on the vegetative market in Israel in the two future periods, examining changes in land use, output prices, farming revenues, net agricultural profitability, shadow values of land and water constraints, consumer surplus and social welfare.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Costanza et al [1997] suggested to introduce the monetary value of environmental services in cost-benefit analyses for judging the feasibility of public projects. Including the evaluation of ecosystem services in the management of environmental resources is a widely recognized need [Daily, 1997;Guo et al, 2000;Ricketts et al, 2004;Kan et al, 2009;Gallai et al, 2009]. However, pricing the natural capital is not easy and requires the use of complex techniques (replacement cost techniques, influence on market-price goods, or willingness to pay for nonmarked commodities).…”
Section: Introductionmentioning
confidence: 99%